PhET Simulation Worksheet for Momentum and Impulse Learning Using the POE2WE Model - Ridho, Muhamad Aqil; Khusaini, Khusaini; Sunaryono, Sunaryono (Department of Physics Education, Universitas Mataram, 2024)
This study examines the feasibility and student responses to worksheets based on PhET simulations integrated with the POE2WE (Predict, Observe, Explain, Elaborate, Write, Evaluate) learning model for teaching momentum and impulse. The research employed a 4D development model and involved expert validators, practitioners, and 30 eleventh-grade students from a high school in Pasuruan. Data were collected using validation and student response questionnaires and analyzed descriptively. The results indicate that the developed worksheets were highly feasible for use in physics learning, as reflected in the validation score of 87.6%, categorized as